Glass nanocomposites : synthesis, properties and applications - Karmakar, Basudeb; Rademann, Klaus; Stepanov, Andrey L. (Elsevier, 2016)
Annotation This volume provides the latest information on a rapidly growing field of specialized materials, bringing light to new research findings that include a growing number of technologies and applications. With this growth, a new need for deep understanding of the synthesis methods, composite structure, processing and application of glass nanocomposites has emerged. World renowned experts in the field build a bridge between the areas of nanoscience, photonics, and glass technology.
Keywords: Nanocomposites (Materials); Nanostructured materials.; Glass.; elektronické knihy; electronic books